Industrial and Biomedical Applications Biobased Polymers of Polylactic Acid and Polyhydroxybutyrate: A Review - Abubakar A. IBRAHIM; Fatimah Y. GARBA; Fatimah A. MUHAMMAD; Ismail B. ADEFESO; Bello A. ISAH; Jacob OLAYIWOLA (FUDMA Journal of Engineering and Technology, 2025)
Polymers have been widely used by mankind for centuries in the form of textiles, ammunition, coatings, and adhesives. With the industrial revolution came widespread applications in plastic packaging, construction and electronics, as well as medical and agricultural applications. Their increased use has resulted in environmental pollution, triggering the search for innovative and eco-friendly bioengineered alternatives. This paper studies the industrial and biomedical applications of Polylactic acid (PLA) and polyhydroxybutyrate (PHB), which are bioengineered polymers designed to harness favourable characteristics of natural and synthetic polymers while minimizing undesirable environmental implications. These bioengineered polymers are commonly utilized in the production of biodegradable packaging materials for reduced environmental pollution and in medical capsules for safe and targeted drug delivery. The study showed that polylactic acid is more suited to applications in packaging and fabrication due to its chemical similarity with fossil-based counterparts such as polyvinyl chloride and polypropylene, while polyhydroxyalkanoates find greater application in pharmaceutical and medical applications due to their biocompatibility and degradation in animal or cell hosts. Both PLA and PHB were found to feature promising industrial prospects due to rising demands influenced by increased environmental awareness. However, their large-scale adoption is threatened by high production costs and scalability challenges which can be addressed by further research on efficient resource utilization, property enhancement and process optimization.
Keywords: Biopolymers, bioengineered polymers, polylactic acid, polyhydroxyalkanoates, polyhydroxybutyrate.